2006
DOI: 10.3189/172756406781811745
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of thin Sea-ice thickness from NOAA AVHRR data in a polynya off the Wilkes Land coast, East Antarctica

Abstract: Antarctic coastal polynyas are major areas of intense ocean–atmosphere heat and moisture flux, and associated high Sea-ice production and dense-water formation. Their accurate detection, including an estimate of thin ice thickness, is therefore very important. In this paper, we apply a technique originally developed in the Arctic to an estimation of Sea-ice thickness using Us National Oceanic and Atmospheric Administration (NOAA) Advanced Very High Resolution Radiometer (AVHRR) data and meteorological data in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…The relationship between SSM/I PR values and thin ice thicknesses may have a hemispheric or latitudinal bias due to differences in atmospheric conditions. Tamura et al (2006) examined the relationship between the PR values and the AVHRR thermal ice thicknesses in an Antarctic coastal polynya, where ice thickness data from in situ measurements were simul- Although the data are limited and the standard deviations are not small, the results of the present study are consistent with those of Tamura et al (2006).…”
Section: A Estimation Of Thin Ice Thicknesssupporting
confidence: 90%
See 2 more Smart Citations
“…The relationship between SSM/I PR values and thin ice thicknesses may have a hemispheric or latitudinal bias due to differences in atmospheric conditions. Tamura et al (2006) examined the relationship between the PR values and the AVHRR thermal ice thicknesses in an Antarctic coastal polynya, where ice thickness data from in situ measurements were simul- Although the data are limited and the standard deviations are not small, the results of the present study are consistent with those of Tamura et al (2006).…”
Section: A Estimation Of Thin Ice Thicknesssupporting
confidence: 90%
“…Their estimation is applicable to sea ice with thicknesses Ͻ0.5 m (Yu and Rothrock 1996). Tamura et al (2006) confirmed the validity of the method by using ice thickness data obtained from in situ observations in an Antarctic coastal polynya. The present study follows their method.…”
Section: Datasupporting
confidence: 53%
See 1 more Smart Citation
“…We assume that the heat flux between ice and atmosphere is a sum of net longwave radiation and turbulent heat flux. The similar ice thickness estimations using AVHRR data were made in the Beaufort Sea, Greenland Sea, Bering Sea, and off East Antarctica [ Yu and Rothrock , 1996; Drucker et al , 2003; Tamura et al , 2006], and these studies showed that the method can estimate ice thickness within the error of ±0.05 m from comparisons with in situ observed ice thickness. Figure 2b shows the AVHRR ice thickness.…”
Section: Amsr‐e Thin Ice Thickness Algorithmmentioning
confidence: 66%
“…For PR36 of 0.057-0.083 (h36 of 10-20 cm), the RMSD for all polynyas is 5.8 cm, and the biases (hi minus h36) range from -3.6 to 1.6 cm among the three polynyas. As in the case of the AMSR-E thin ice thickness algorithm [19], the values of these deviations and biases are generally within the accuracy of hi (about ±5 cm) determined by comparisons with in situ observations [35], [46], [50]. Therefore, we used (3) and (4) as a unified algorithm for the estimation of thin ice thickness from AMSR2 data over the entire Antarctic Ocean.…”
Section: A a Thin Ice Thickness Algorithmmentioning
confidence: 81%